Analyzing and Designing Decision Support Systems for Stroke Patient Daily Treatment - Anik Hanifatul Azizah; Mira Asmirajanti; Ariq Pratama (Politeknik Pertanian Negeri Samarinda, 2024)
Stroke is one of the neurological diseases that often requires complex management and treatment. Making the right decisions in diagnosing and treating stroke patients can have a significant impact on the recovery process and the quality of life for patients. To assist healthcare professionals and patients in making more informed decisions, this research has developed the